TYPOLOGY AND FUNCTIONS OF REPETITION IN MARINA TSVETAEVA'S POETIC DISCOURSE. - Madina Ildarovna Khannanova (International Journal of Literature and Language Studies, 2026)
The article "Characteristics of types of repetitions in the poetic discourse of M.I. Tsvetaeva" discusses the use of repetitions in the poetry of Marina Ivanovna Tsvetaeva. The authors analyze various types of repetitions, including epiphora, anaphora, epanaleps, alliteration and others, and describe their functions in Tsvetaeva's poems. The results of the study allow us to conclude that repetitions play a significant role in Tsvetaeva's poetic discourse, creating a special musicality and emotionality in her poems. The authors also note that repetitions are used not only to enhance the effect, but also to convey deep meaning and ideas, enhance the expressiveness and emotionality of works. In general, this article may be useful for researchers of M.I. Tsvetaeva's poetry, as well as students and teachers of literary courses studying the mechanisms of poetic expressiveness and techniques of working with language.